2004
DOI: 10.1016/j.jvs.2004.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Limb salvage after infrainguinal bypass graft failure

Abstract: The overall prognosis for limb salvage in patients with failed infrainguinal bypass grafts is poor, particularly in patients with grafts placed because of tissue loss and those with early graft failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 46 publications
1
35
1
2
Order By: Relevance
“…As occlusion of infrainguinal bypass grafts is associated with impaired limb salvage (25), repeated revascularization may be important to grant clinical success. Therefore, routine clinical and sonographic surveillance remain necessary to prevent graft occlusion (5).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the long-term patency rate for a single-segment autologous vein ranges from 23% to 85% compared with that for prosthetic grafts from 11% to 39% [11]. Autologous venous grafts, such as that of the great saphenous vein, are preferred as ideal substitutes for arterial reconstruction because of the greater biocompatibility, long-term patency and lesser number of complications [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%